2013
DOI: 10.4271/2013-01-2400
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Characterization of School Bus Drive Cycles Collected via Onboard Logging Systems

Abstract: In an effort to characterize the dynamics typical of school bus operation, National Renewable Energy Laboratory (NREL) researchers set out to gather in-use duty cycle data from school bus fleets operating across the country. Employing a combination of Isaac Instruments GPS/CAN data loggers in conjunction with existing onboard telemetric systems resulted in the capture of operating information for more than 200 individual vehicles in three geographically unique domestic locations. In total, over 1,500 individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…Findings regarding route distances were reported inDuran et al (2013), which analyzed over 1,700 route shifts from the school buses available in Fleet DNA that were available at its time of publication[36]. This study found those route shifts averaged 32 miles and had a large spread, from 1 to 128 miles; this result was similar to a 2011 study considering 861 route shifts in Fleet DNA finding an average length of 35 miles[37].…”
supporting
confidence: 65%
“…Findings regarding route distances were reported inDuran et al (2013), which analyzed over 1,700 route shifts from the school buses available in Fleet DNA that were available at its time of publication[36]. This study found those route shifts averaged 32 miles and had a large spread, from 1 to 128 miles; this result was similar to a 2011 study considering 861 route shifts in Fleet DNA finding an average length of 35 miles[37].…”
supporting
confidence: 65%
“…The paper analyses the second-bysecond emission results of FTIR measurements to investigate which parts of the test cycles are causing the highest emissions. [70] The methodology of a large-scale duty-cycle statistical analysis are presented, including graphical and tabular representations of a number of relationships between key duty-cycle metrics observed within the larger data set in [71]. Examining a number of metrics associated with vehicle energy consumption and driving behaviour, statistical relationships between key metrics of interest were explored.…”
Section: Data Processing Softwarementioning
confidence: 99%
“…Examining the correlation between average driving speed and kinetic intensity, one observes a strong power correlation between the two variables. [71] Extensive duty-cycle statistical analyses are performed to examine and characterize common vehicle dynamics trends and relationships based on in-use field data in [72]. Having received in-use data, the data are processed using a series of semi-automated routines.…”
Section: Data Processing Softwarementioning
confidence: 99%